Pengaruh Knowledge Sharing terhadap Innovative Behavior dengan Absorptive Capacity sebagai Variabel Intervening (Studi pada Karyawan PT Sai Apparel Industries Semarang) - Aisya Sita Dewi; Intan Ratna Wati (Dinasti Review, 2024)
This study aims to determine and analyze the influence of Knowledge Sharing (KS) on Innovative Behavior (IB) through the mediating role of the Absorptive Capacity (AC) variable in one of the manufacturing companies operating in the garment sector, namely PT Sai Apparel Industries Semarang. The data collected were primary data originating from the distribution of research questionnaires and short interviews with several employees who were research respondents, as well as secondary data obtained through journals, websites, books, and other relevant sources from the company. The sampling technique in this study used a snowball sampling technique involving 100 employees as respondents. The data that have been obtained are then analyzed using Partial Least Square (PLS) with the SmartPLS 3.2.9 application to test the hypothesis and the influence of the relationship between variables. The results of this study show that Knowledge Sharing (KS) has a positive and significant effect on Innovative Behavior (IB), Knowledge Sharing (KS) has a positive and significant effect on Absorptive Capacity (AC), and Absorptive Capacity (AC) has a positive and significant effect on Innovative Behavior (IB). The findings in this study also prove that Absorptive Capacity (AC) has a positive and significant influence as an intervening variable between the relationship between Knowledge Sharing (KS) and Innovative Behavior (IB).